An update on allergy and anaphylaxis in pediatric anesthesia. Issue 9 (4th August 2019) - Stepanovic, Bojana; Sommerfield, David; Lucas, Michaela; von Ungern‐Sternberg, Britta S.
Abstract: Childhood allergy is common, and increasing. Many children are incorrectly labeled as having allergy or adverse drug reactions. This can pose a dilemma for anesthetists and lead to a change in practice or drug selection. We review the pathophysiology of hypersensitivity reactions and the implications for anesthesia of food allergy, atopy, and family history of allergy in children. The epidemiology of anaphylaxis is discussed. We discuss the common triggers of perioperative anaphylaxis in children and explore emerging triggers including chlorhexidine and sugammadex. Accurate data on pediatric perioperative anaphylaxis is limited worldwide, with marked geographic variation. This highlights the need for accurate local, district and/or nationwide incident reporting. The clinical features, diagnosis, and management of anaphylaxis under anesthesia are discussed. We review the process of expert allergy testing following a suspected case of anaphylaxis to guide future safe anesthesia administration. The preoperative consultation is an opportunity for referral for allergy testing to allow de‐labeling. This has the potential for improved antibiotic stewardship and more effective treatment with first‐line therapeutic agents.